Silent night [videorecording (DVD)] - Griffin, Camille; Knightley, Keira, 1985-; Goode, Matthew, 1978-; Griffin Davis, Roman, 2007-; Depp, Lily-Rose, 1999-; Wallis, Annabelle, 1984- (AMC, RLJE Films, 2022)
A group of old friends, in true British fashion and while the rest of the world faces impending doom, reunite to celebrate Christmas in the comfort of an idyllic country home. Burdened with the inconvenience of mankind's imminent destruction, they adopt a stiff upper lip, crack open another bottle of prosecco and continue with their festivities. But no amount of stoicism can replace the courage needed for their last night on Earth.